"ERGONOMIZATION" OF THE WORKING ENVIRONMENT AND BUILDING UP OF HEALTHY WORKING POSTURE OF DENTAL STUDENTS - Lydia G. Katrova; Ivan Ivanov; Marin Ivanov; Кalina Pejcheva (Peytchinski Publishing, 2012)
The purpose was to assess the knowledge of dental students of the ergonomics' principles and how they develop adequate skills to work safe in clinic. Methods: A questionnaire, comprising a set of 25 close-ended questions and 2 open-ended questions to rate the knowledge, attitude and motivation regarding the good posture, training environment and real clinical practice' organization, was distributed among 260 from a total of 685 dental students. Demonstration of proper working posture and training in it had been given to 4-th and 5-th year' students. The process was registered by photos. Data were treated statistically using SPSS. 16.1. Results: Most of students report they know the right working posture (52,6%) or "have an idea" (36,6%). Almost all of them are persuaded it is important to work in good posture (95,9%). They would like to be trained in ergonomics (96,4%), and think it should be done before graduation (90,2%). Students agree on integrating ergonomic training into the clinical training and think it is possible (73,6%). The students originating from "dental" families demonstrated higher interest in ergonomics. The photos taken before the training showed that knowledge without practice is not stable. Conclusion: The students understand the importance of the practical application of the dental ergonomics principles. Registering skills is an important education tool. The findings of the research support the argument for integrating ergonomics in clinical studies.